i have to understand the example for me to be able to answer my assignment problems 4 and 5. Your explanation is waaaaay better than my instructor's:

indeed.

Looking at one line... To explain....

The second line has the values of x=0, y=0 and z=1

in the explanation ... The function f is = x'y'z = x'*y'*z

>> the terms are multiplied to gether

the value of x' is 1

the value of y' is 1

the value of z is 1

so the result of f = x'y'z = 1*1*1 = 1

it would seem that you are not seeing how the functions f and g and h are described in the write up.

Look clearly into the values of the functions...

Onward
he didn't say that f values are given already. He just "rephrased" the example. Which i still don't get it, and yes he explains like that too, like a robot. It drives me crazy haha

this is my assignment by the way:

this is what i did (don't mind the note i have on the bottom part, that's what i asked my professor again and again):